2020
DOI: 10.1108/jhti-04-2020-0053
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the development of the Iranian tourism market employing a MICMAC approach: a new long-range planning method to attract the ASEAN international tourist market

Abstract: PurposeAs tourism development is an unquestionable part of every national growth policy, this study aims to introduce an integrated method employing MICMAC analysis for understanding the key strategic variables of Iran's tourism development system.Design/methodology/approachThe structural analysis with MICMAC method was used to determine the classification of variables, aimed at structuring ideas to deal with complex decision-making and help planners and policymakers formulate future-based strategies.FindingsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Iran's DI is not specific to tourism and is closely linked to political propaganda and the country's relationships with other countries (Akhoondnejad, 2015). Therefore, Iran needs to consider a profit‐based approach in its international relations (Nematpour, Khodadadi, Rezaei, et al, 2021). On the other hand, peace, comfort, and security in Iran are among the most critical factors in attracting tourists (Ghasemi et al, 2014) because tourists' perceptions of safety, security, and risks have an impact on the destination's image (Khan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iran's DI is not specific to tourism and is closely linked to political propaganda and the country's relationships with other countries (Akhoondnejad, 2015). Therefore, Iran needs to consider a profit‐based approach in its international relations (Nematpour, Khodadadi, Rezaei, et al, 2021). On the other hand, peace, comfort, and security in Iran are among the most critical factors in attracting tourists (Ghasemi et al, 2014) because tourists' perceptions of safety, security, and risks have an impact on the destination's image (Khan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…From the supply side, Iran is a force consisting of all products and services available at the destination at any given time (Formica & Uysal, 2006). To contribute to the country's attractiveness as a destination, the Iranian tour operators need to diversify the incoming tours by considering specific destinations (Nematpour, Khodadadi, Rezaei, et al, 2021) for international tourists. Furthermore, integrating products and services based on culture and heritage into tourism is important in improving a destination's attractiveness (Pallavicini, 2017), particularly through the built environment, which is recognized as an important heritage to enhance the tourist experience (Moulin, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mehraliyev et al (2022) confirmed that corporate strategic management is followed in resorts and hotels. Nematpour et al (2021) attempted to identify critical developmental variables, like tourism planning and policy-making for the Iranian tourism sector.…”
Section: Stages Of Talcmentioning
confidence: 99%
“…While tourism growth is likely to continue, the natural resources that make destinations attractive to tourists do not expand but risk being lost and taking a long period to replenish (Hübler, 2019). Sustainable and practical solutions (Tahbaz, 2016) and the implementation of long-term tourism planning (Nematpour, Khodadadi, Rezaei, & Makian, 2020) are required to address the challenges caused by the destruction of biodiversity in Iran.…”
Section: Environmental Challengesmentioning
confidence: 99%